2012
DOI: 10.1017/s0007114512003224
|View full text |Cite
|
Sign up to set email alerts
|

Sheep cheese naturally enriched in α-linolenic, conjugated linoleic and vaccenic acids improves the lipid profile and reduces anandamide in the plasma of hypercholesterolaemic subjects

Abstract: Intake of dairy fat has long been considered as a risk factor for CVD. Pasture and dietary lipid supplementation have been reported to be reliable strategies in ruminant nutrition, in order to increase the content of a-linolenic acid (ALA), conjugated linoleic acid (CLA) and vaccenic acid (VA), and decrease SFA in milk fat. In the present study, we aimed at verifying whether consumption of a sheep cheese, naturally enriched in ALA, CLA and VA, would modify the plasma lipid and endocannabinoid profiles in mildl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 63 publications
4
106
0
3
Order By: Relevance
“…However, the predictive ability of these nutritional indexes needs to be enhanced, by using new formulas which take into account other FAs (e.g. CLA and VA), considering that Pintus et al (2012) have recently reported a negative association between CLA in the diet and blood cholesterol level in humans.…”
Section: Liver and Kidney Metabolic Markersmentioning
confidence: 99%
“…However, the predictive ability of these nutritional indexes needs to be enhanced, by using new formulas which take into account other FAs (e.g. CLA and VA), considering that Pintus et al (2012) have recently reported a negative association between CLA in the diet and blood cholesterol level in humans.…”
Section: Liver and Kidney Metabolic Markersmentioning
confidence: 99%
“…Recent human studies showed beneficial effects of dietary intake of dairy products naturally enriched with cis(c)9,trans(t)11-CLA, such as a decrease in plasma cholesterol level (Pintus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, great attention has focused on conjugated linoleic acid (CLA), PUFAn3 and long chain FA, which have several benefits to human health. Biochemical studies showed beneficial effects of the cis9, trans11 CLA, against neoplastic and atherosclerotic processes (Bhattacharya et al, 2006;Sofi et al, 2009) as well as a cholesterol lowering effect (Pintus et al, 2012). Epidemiological studies evidenced that, among PUFAn3, C18:3n3 is associated with a reduced risk of cardiovascular diseases (Roth and Harris, 2010), whereas its elongation products, EPA and DHA, has beneficial effects on proper brain and visual development in the fetus, and maintenance of neural and visual tissues throughout life (Ruxton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%